IMPLEMENTASI PEMBELAJARAN BAHASA JAWA BERBASIS PAILKEM DI KELAS 3 SEKOLAH DASAR (Joyful Learning Journal, 2018)
Based on preliminary observation can be seen that the teacher in grade 3 Elementary School Gugus Pringgodani Banyumanik District Semarang in the learning still using traditional models and methods and do not use the media in the learning process. The purpose of this study was to determine whether the third grade teacher of Primary School Gugus Pringgodani Banyumanik Sub-district Semarang City has been using the learning strategy of PAILKEM. The method used is the case study method of observation and analyzed using interactive model according to Miles and Huberman. The steps in analyzing this data are (1) data collection, (2) data reduction, (3) data display, and (4) conclusion or verification. Based on the research, it can be concluded as follows: (1) grade 3 teacher of Gugus Pringgodani Sub-District of Banyumanik Semarang City has implemented PAILKEM learning strategy but not all indicator of PAILKEM appears, (2) in implementing learning strategy of PAILKEM grade 3 teacher SD Gugus Pringgodani Kecamatan Banyumanik Kota Semarang has been categorized both in implementing the learning of PAILKEM but not all indicator of PAILKEM implemented, (3) there is influence of learning strategy used by teacher to the respondents of learning result of grade 3 students of SD Pringgodani Cluster Banyumanik Sub-district Semarang City. In general, the 3rd grade teachers in implementing the PAILKEM learning have been categorized well but not all PAILKEM indicators are met, contained in Environmental, Innovative and Creative indicators.